EFFECT OF SETHOXYDIM HERBICIDE IN THE LEAF ANATOMY AND PHYSIOLOGY OF BRACHIARIA GRASS UNDER WATER STRESS - PEREIRA,M.R.R. (2017)
ABSTRACT The goal of this study was to analyze the leaf anatomy and physiological behavior of Brachiaria grass plants (Urochloa decumbens) under different water conditions and with the application of sethoxydim herbicide. The used experimental design was the completely randomized one, with four replications, consisting of a 3 x 2 factorial scheme, with the combination of three water managements (-0.03, -0.07 and -1.5 MPa) with and without the application of sethoxydim herbicide + Assist mineral oil, at the recommended dose for the species (184 g a.i. ha-1). The assessed physiological and anatomicalal parameters were photosynthetic rate, stomatal conductance, transpiration, difference between leaf and room temperature, dry mass of plants, thickness of bulliform cells, adaxial and total epidermis. Under the conditions in which the experiment was conducted, it appears that Brachiaria grass leaves showed uniseriate epidermis, homogenous mesophyll, with radiated distribution of parenchymal cells around the vascular bundles. The adaxial epidermis presented bulliform cells; the vascular bundles are collateral and are present in different sizes. Water stress had a negative influence on herbicide effectiveness and decreased all physiological parameters. The application of the herbicide caused anatomical changes in plants with no water stress (-0.03 MPa), such as limitations in the growth of epidermic and bulliform cells, and in the total leaf thickness. However, in treatments with stress (-0.07 and -1.5 MPa), there were no differences in leaf anatomy, but an increase in the total thickness of leaves, probably as a result of the water stress conditions to which plants were submitted..